2011
DOI: 10.1007/s10029-011-0791-3
|View full text |Cite
|
Sign up to set email alerts
|

Parastomal hernia repair outcomes in relation to stoma site with diisocyanate cross-linked acellular porcine dermal collagen mesh

Abstract: For parastomal hernias within the rectus sheath, diisocyanate cross-linked porcine dermal collagen mesh onlay repair gives good results and is safe to use. Repair of a parastomal hernia where the stoma is lateral to the rectus sheath has a significantly higher risk of recurrence and is not recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…several small retrospective reviews of parastomal repairs using bioprosthetic materials for reinforcement have reported hernia recurrence rates between 7% and 27%. [118][119][120][121][122] however, follow-up in these studies was short (9-18 months). further comparative studies with longer follow-up are needed to establish the efficacy and cost-effectiveness of bioprosthetic materials in this setting.…”
Section: Ostomy Complicationsmentioning
confidence: 88%
“…several small retrospective reviews of parastomal repairs using bioprosthetic materials for reinforcement have reported hernia recurrence rates between 7% and 27%. [118][119][120][121][122] however, follow-up in these studies was short (9-18 months). further comparative studies with longer follow-up are needed to establish the efficacy and cost-effectiveness of bioprosthetic materials in this setting.…”
Section: Ostomy Complicationsmentioning
confidence: 88%
“…No head-to-head studies have compared mesh types in the context of repair, and the role of porcine dermal meshes has been confined to case series 37,49,50. One small randomized trial has demonstrated the efficacy of porcine dermal meshes for the prevention of parastomal hernias,51 but, in general, the infective complications with synthetic mesh in this context have been low 52.…”
Section: Stomal Herniamentioning
confidence: 99%
“…Extra-peritoneal repair with mesh results in infection rates as high as 37 %, and infection is the main complication [11,26,27]. When comparing onlay and sublay techniques by pooling results from multiple large studies, onlay mesh position is associated with higher recurrence rate (22.3 vs. 4.6 %) [13,17,21,[27][28][29][30][31][32] (Table 1). Rate of wound infection was also higher with sublay mesh placement (likely contributed by more extensive tissue dissection).…”
Section: Mesh Repair Of Parastomal Herniasmentioning
confidence: 99%
“…There are no studies that specifically address outcomes of PHR in contaminated fields, as many studies evaluated PH in the context of other abdominal hernia surgeries [20,21,[23][24][25][26]. In studies evaluating PHR with biologic mesh collectively with other hernia repairs in contaminated settings, wound-related morbidity ranged widely (17-66 %) as did hernia recurrence (9-33 %); however, there were no meshrelated complications requiring mesh removal [19,20,[22][23][24].…”
Section: Synthetic Versus Biologic Prosthesesmentioning
confidence: 99%
See 1 more Smart Citation